Polycystic ovary syndrome risk: efficacy of self-assessment test - Taneja, Jyoti; Arora, Taruna; Jain, Anju; Mansukhani, Chandra; Bhalla, Latika; Nanda, Sarita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Polycystic ovary syndrome (PCOS) is a growing morbidity in young women globally. This disease has an association with several exogenous factors like irregularity of menses, hirsutism and obesity. Very few standardized self-assessment tools based on easily observable factors are available for use in the Indian population, which can help them to assess their PCOS risk accurately. Methods: Undergraduate women of the age group 18-22 years enrolled in a university campus participated in the survey questionnaire. Nineteen questions with binary answers as “yes” or “no” were used for self-assessment test. Each “yes” was scored as one mark, and each “no” scored as zero, leading to the maximum score of 19. Scores of the women with irregular menses (test group) were compared to those of regular menses (control group). Welch’s corrected t-test was used to calculate the significance at 5% between the groups. The clinical assessment confirmed the presence or absence of PCOS condition. Results: One thousand and fifty-four women participated in the study. The study showed that 262 (24.8%) of young women reported irregular menstrual cycle. The average total score of the control group was 3.07±2.35, whereas that of the women with irregular menses was 5.93±2.86. 21 out of 28 participants, who scored high, were diagnosed with PCOS, on clinical assessment by Rotterdam criteria. Conclusions: The self-assessment test can assess the risk of PCOS. This test has 75% sensitivity and accuracy in predicting the presence of PCOS.